Literature Review of the Flipped Classroom - Deng, Fei (Theory and practice in language studies, 2019)
On the basis of the brief history of the Flipped Classroom, this paper explains different scholars’ definition of the Flipped Classroom. And then it introduces the theoretical basis, which is Benjamin Bloom’s Mastery Learning, including core idea, processing procedures, evaluation, and the educational significance of Mastery Learning in the Flipped Classroom. After that the paper makes a comparative analysis between the Traditional Classroom and the Flipped Classroom. At last it reviews the previous studies on the Flipped Classroom abroad, theoretical and practical studies on Flipped Classroom at home.